A dual-functional luminescent Tb(iii) metal–organic framework for the selective sensing of acetone and TNP in water. Issue 20 (16th March 2018) - Goel, Nidhi; Kumar, Naresh
Abstract : A novel 2D luminescent terbium metal–organic framework demonstrating highly efficient and selective sensing for acetone and 2, 4, 6-trinitrophenol (TNP) in an aqueous solution was solvothermally synthesized and structurally characterized. Abstract : Herein, a novel water-stable luminescent terbium metal–organic framework, {[Tb(L1 )(L2 )0.5 (NO3 )(DMF)]·DMF} n (TPA-MOF), with 1, 10-phenanthroline (phen) and 3, 3′, 5, 5′-azobenzene-tetracarboxylic acid (H4 abtc) ligands was solvothermally synthesized and structurally characterized. TPA-MOF possesses a two-dimensional (2D) extended framework featuring an 8-connected uninodal SP2-periodic net topology with the Schläfli point symbol of {3^12;4^14;5^2}. The π-electron rich luminescent TPA-MOF exhibits four characteristic emission bands of Tb 3+ ion and acts as a selective and sensitive probe for acetone as well as the electron deficient 2, 4, 6-trinitrophenol (TNP). Moreover, gas sorption studies confirm that TPA-MOF displays ultra-micropores and adsorbs moderate amounts of N2 and CO2 .